Trade Effects of Exchange Rates and their Volatility: Chile and New Zealand - Huchet-Bourdon, Marilyne (OECD Trade Policy Papers, 2012)
Trade deficits and surpluses are sometimes attributed to intentionally low or high exchange rate levels. The impact of exchange rate levels on trade has been much debated but the large body of existing empirical literature does not suggest an unequivocally clear picture of the trade impacts of changes in exchange rates. In addition, much of the evidence on this subject considers currencies of large economies, and overwhelmingly the United States.This study examines the impact of exchange rates and their volatility on trade flows in two small, open economies - Chile and New Zealand - with three major trading partners, in two broadly defined sectors - agriculture on the one hand and manufacturing and mining on the other. It finds that exchange volatility impacts trade flows in the small, open economies more than was found for larger economies. Findings do not clearly indicate the direction of the impact, i.e. whether this volatility increases or decreases trade in all countries and sectors. Exchange rate levels, on the other hand, affect trade in both agriculture and manufacturing and mining sectors although their magnitude differs depending on the trading partner and sector. Moreover, this study indicates that a depreciation in the exchange rates in Chile and New Zealand would not lead to a strong change in their trade balances with three main trading partners across the board